1984
DOI: 10.1002/apmc.1984.051280101
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zur Thermoanalyse von Harnstoff‐Formaldehyd‐Schäumen

Abstract: ZUSAMMENFASSUNG:Differentialthermogravimetrische Untersuchungen an Harnstoff sowie an Monound Dimethylolharnstoff mit anschlieoender Auswertung durch IR-spektroskopische Analysen ergaben charakteristische differentielle Zersetzungsmaxima von Methylolgruppen und primlren Amidogruppen.Vergleichende thermische Abbauversuche an Harnstoff-Formaldehyd (UF)-Vorkondensaten und den daraus hergestellten Schlumen zeigten, dao ausgehartete UF-Schaume keine nachweisbaren Mengen an reaktiven Methylolendgruppen mehr enthalte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…(2) From 250 to 300°C, an oxidative degradation of methylurea units seems to occur. (3) From 350 to 400°C, i.e., an oxidative degradation of melamine units,48, 49 as the degradation process of resin and cellulosic blends by breaking the bonds release oxygen, which is used for oxidative degradation (4) demarcates the degradation of the residual fraction that starts from 450°C. It is evident that methylurea methylol undergoes an oxidative degradation at lower temperature than those of the melamine ones.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) From 250 to 300°C, an oxidative degradation of methylurea units seems to occur. (3) From 350 to 400°C, i.e., an oxidative degradation of melamine units,48, 49 as the degradation process of resin and cellulosic blends by breaking the bonds release oxygen, which is used for oxidative degradation (4) demarcates the degradation of the residual fraction that starts from 450°C. It is evident that methylurea methylol undergoes an oxidative degradation at lower temperature than those of the melamine ones.…”
Section: Resultsmentioning
confidence: 99%
“…But due to the superior quality of resin and simplicity in preparation, the melamine–urea–formaldehyde (MUF) polycondensates are in use as adhesives for pulpwoods,29–35 IR36 and NMR37–42 spectroscopy have investigated their structures. An enormous studies on MUF,43–47 melamine–formaldehyde,48 melamine–urea, and urea–formaldehyde49 have been conducted in detail, while studies on MMUF resin preparation and its blends with cellulosic items have not been reported. This manuscript reports the structural, morphological, and thermal stability investigations on the resin and its blends.…”
Section: Introductionmentioning
confidence: 99%
“…How do the molecules maintain identity under different polarity and electrostatics for sequential structural reorientations? It becomes more important in case of biomolecules such as EPC which being weakly polar involved in biosensor signal as emulsifying agent (9)(10)(11). For example, a detection of bound water at moon is an input and incentive to intensify search and research of undiscovered molecular world (12).…”
Section: Detailed View Of Biosensor Mechanismmentioning
confidence: 99%
“…It forms many channels and cavities 12,13 to trap foreign material like boron neutron capture therapy 14 and many others 9, 14-17 in medical sciences, drug delivery systems, biomedical, biophysical, and biochemical 9,18 fields using friccohesity, a dual force theory (DFT) with respect to chiral friccohesity. The molecules are biodegradable in nature with respect to polar solvent 1 and also ecofriendly.…”
Section: Introductionmentioning
confidence: 99%